Capitalism in Philosophical Posthumanism - Imanaka, Jessica Ludescher (Journal of Posthumanism, 2021)
Francesca Ferrando’s Philosophical Posthumanism offers a monumental contribution to the scholarly, teaching, and practitioner worlds. It spans multiple dimensions of posthumanism and integrates them into a compelling account of this invigorating shift in theory and praxis. The book has value for scholars, teachers, and newcomers of/to the posthuman r/evolution(s) thanks to its prodigious scope and insightful analyses. I believe it should be a top consideration in any reading list for a serious course of study on posthumanism. In what follows, I will offer comments to inspire ongoing engagement with this potent text, intervening from my own background in business ethics and political economy.